Voltage regulation, power balancing and battery storage discharge control by smart demand side management and multi-objective decision making - Shahnia, Farhad; Wishart, M.T.; Ghosh, A. (University of Tasmania, 2013)
A novel intelligent online demand side management system is proposed for peak load management. The method also regulates the network voltage, balances the power in three phases and coordinates the battery storage discharge within the network. This method uses low cost controllers with low bandwidth two-way communication installed in costumers' premises and at distribution transformers to manage the peak load while maximizing customer satisfaction. A multi-objective decision making process is proposed to select the load(s) to be delayed or controlled. The efficacy of the proposed control system is verified through an event-based developed simulation in Matlab.